Verbalizações de mães referentes aos seus sentimentos empáticos - Assis, Natália Lins Pequeno de (2011)
Empathy, according to Martin Hoffman’s studies, is understood as an affective response in a situation oriented more to another person state than to its own state. It is considered that the procedures adopted by parents in education is crucial to strengthen or weaken feelings of empathy. When parents verbalize feelings and explain the situation of the victim calling attention to their suffering, they stimulate the child's empathic tendency and create conditions for carrying out pro-social behavior, help, generosity, etc.. Understanding the importance of empathic ability and the role of the parents for its strengthening, the general aim of this study is to verify mother’s empathic feelings of different socio-economic status, the situations that can cause these feelings, what they say to their children about these feelings and how they do it. To achieve this goal 100 literate women participated in the research, they are mothers of children and adolescents who attended public and private schools in the city of João Pessoa-PB. Participants were equally distributed in relation to gender, age and children´s school context. Mothers participants completed a semi-structured interview with questions pertaining to situations involving a victim and an abuser. The results found in the semantic content analysis indicated that : the feelings verbalized by mothers in situations were: Compassion, Anger, Guilt and Injustice; mothers, when talking to their children, gave more recommendations than explanations, the most frequent recommendations were: help another person, not hurt and be generous, the most frequent explanations were: explicit the reason of suffering, the situation of aggression and injustice as well as clarify the value of helping; situations that made mothers have more empathic feeling were: Tragedy / illness / death and poverty. The results of lexical analysis indicated the formation of four classes presented in two groups. The first group, Contexts related to empathy, joined Classes 1 (situations evocative of empathy) and 4 (family structure). The second group, empathic feelings, brought together the two classes (feeling of empathic injustice - role-taking) and 3 (empathic feelings - pro-social behavior). In classes 1 and 4 we have mothers explanations about how their family dynamics worked and their experiences with their empathetic feelings in everyday life. In classes 2 and 3, there was a separation of empathic feeling of injustice of others feelings. In general, it was found that: the empathic feelings verbalized by mothers were the same of what Hoffman worked on his theory, they talked with their children and worried about their social and moral development, however, they were more concerned to recommend and guide their children's behavior than to clarify the situation, explain the origin of certain feeling toward the other person or talk about the importance of trying to understand people around them.